NEW BIOTYPE OF Trichoderma spp EFFECTIVE IN PRODUCTION OF SOME PLANT GROWTH REGULATORS - Kahld Hassan Taha (Mesopotamia Journal of Agriculture)
In order to produce a new biotype effective in enhancement of some growth regulators, seven isolates of the indigenous fungus Trichoderma harzianum, Thk20, Thk80, Th1, Th2, Th3, Th4, Th5 and T.viride were used. The most effective Trichoderma spp. isolate was Thk20 in producing GA3 and IAA with an amount 44.34 and 33.71 mg/L respectively. The results showed the ability of some isolates to improve plant growth through enhancing IAA and GA3 biosynthsis: Isolates Thk20, Th1 and T.viride increased GA3 content to 905.46, 944.18 and 597.29 ng /g F.W. respectively, while the isolate Thk20, Thk80 and T.viride increased IAA content to 682.33, 347.85 and 795.6 ng /g F.W. respectively. Thk20 spores were exposed to UV aiming a new biotypes .The new biotypes were tested for their efficiency as a plant growth promoter. The biotypes N9,N15,and N22 exceeded the other biotypes parent isolate for it's GA3,IAA production with an amount 57.34,44 and 44.5 mg/L respectively while in parent isolate was 31.58 mg/L for GA3 and 44.1,39.52and 33.39 mg/L respectively. while in parent isolate was 28.71 mg/L for IAA.